PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH, PEMANFAATAN SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA MALANG - Lailatur Rohmah; Noor Shodiq Askandar; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of understanding government accounting standards, the utilization of regional financial accounting information systems and internal control systems on the quality of financial reports in Malang city government. The population in this study were employees of the Accounting and Administration Division of Regional Assets in BPKAD Malang, totaling 69 people. The technique used in sampling is purposive sampling technique. The sample chosen was 42 respondents. Data was collected using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 20 (Product Statistics and Service Solutions version 14). The test data used is the simultaneous hypothesis test (f), the coefficient of determination (R2), and the partial hypothesis test (t). The results showed that simultaneous independent variables significantly influence the dependent variable. Based on the results of the partial test three variables have an influence on the quality of financial statements, Understanding of Government Accounting Standards (sig = 0.002), Utilization of Regional Financial Accounting Information Systems (sig = 0.031) and internal control systems (sig = 0,000) affect the quality of financial statements.Keywords: Understanding of Government Accounting Standards, Utilization of Regional Financial Accounting Information Systems, Internal Control Systems and Quality of Financial Statements